1989
DOI: 10.1002/jnr.490220409
|View full text |Cite
|
Sign up to set email alerts
|

Role for the oligodendrocyte cytoskeleton in myelination

Abstract: Enriched cultures of rat brain oligodendrocytes were extracted with a buffer that separated the cells into a Triton X-100-soluble fraction and an insoluble cytoskeleton (CSK) residue. The buffer was optimised so that intact microtubules were preserved in the CSK residue. The partition of four myelin proteins between the soluble and the CSK fractions was determined by immunoblotting and immunofluorescence. Immunoblotting showed that two integral membrane proteins of myelin, the proteolipid protein (PLP) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
147
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(163 citation statements)
references
References 38 publications
12
147
0
Order By: Relevance
“…Primary OLGs 1 to 2-days-old rat brain OLGs 12 DIV TX-100 0.5% 3 min RT Wilson and Brophy 1989 30-days-old rat brain TX-100 1% 30 min 4°C Kim and Pfeiffer 2002 Adult rat brain CHAPS 20 mM 2h 4°C Kim et al 1995 Purified myelin 2-year-old mice TX-100 2% 30 min 4°C Saravanan et al 2004 Primary OLGs Mature rat OLGs CHAPS 40 mM 30 min 4°C Kim et al 1995 …”
Section: Mbpmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary OLGs 1 to 2-days-old rat brain OLGs 12 DIV TX-100 0.5% 3 min RT Wilson and Brophy 1989 30-days-old rat brain TX-100 1% 30 min 4°C Kim and Pfeiffer 2002 Adult rat brain CHAPS 20 mM 2h 4°C Kim et al 1995 Purified myelin 2-year-old mice TX-100 2% 30 min 4°C Saravanan et al 2004 Primary OLGs Mature rat OLGs CHAPS 40 mM 30 min 4°C Kim et al 1995 …”
Section: Mbpmentioning
confidence: 99%
“…Mouse OLG 5 DIV CHAPS 20 mM 30 min 4°C 30-days-old rat TX-100 1% 30 min 4°C Kim and Pfeiffer 1999 4-6 weeks old rat TX-100 0.5% 3 min RT Gillespie et al 1989 35-days-old mice TX-100 / CHAPS / Brij 96V / TX-102 1% 30 min 4°C/37°C Taylor et al 2002 2-year-old mice TX-100 2% 30 min 4°C Saravanan et al 2004 TX-100 1% na 4°C Mouse CHAPS 30 mM na 4°C Boyanapalli et al 2005 Rabbit TX-100 1% 16h + 24h 4°C Pereyra et al 1988 Purified myelin Bovine brain E11 -E40 CHAPS 1.5% 30 min 4°C Debruin et al 2005 Primary OLGs 1-2 day old rat brain OLGs 12 DIV TX-100 0.5% 3 min RT Wilson and Brophy 1989 CNP Optic nerve p13, p18, p24 and 2 months old rat TX-100 1% 1h 4°C Maier et al 2005 Primary OLGs premyelinating mouse OLGs TX-100 1% 1h 4°C Schafer et al 2004 TX-100 1% 30 min 4°C Spinal cord Rat (WT or EAE) Lubrol WX 0.5% 30 min 4°C Maier et al 2005 Optic nerve p13, p18, p24 and 2 months old rat TX-100 1% 1h 4°C Schafer et al 2004 35-days-old mice TX-100 / CHAPS / Brij 96V / TX-102 1% 30 min 4°C Taylor et al 2002 Adult mouse brain TX-100 2% 30 min 4°C Krämer et al 1997Krämer et al , 1999 Purified myelin 2-year-old mice TX-100 2% 30 min 4°C Saravanan et al 2004 Mouse OLGs 5/8 DIV TX-100 2% 30 min 4°C Krämer et al 1997Krämer et al , 1999 Primary OLGs Mouse OLG 5 DIV CHAPS 20 mM 30 min 4°C NCAM 120…”
Section: Primary Olgsmentioning
confidence: 99%
“…Although likely to be controlled by the cell cytoskeleton, it is not clear how oligodendrocytes undergo the substantial morphological changes during the different phases of myelination (i.e., axonal recognition, ensheathment, process retraction, wrapping, myelin compaction, and elongation of the myelin unit). The cytoskeleton of oligodendrocytes contains microtubules and microfilaments but appears to be devoid of intermediate filaments (Wilson and Brophy, 1989;Pfeiffer et al, 1993). In cultured oligodendrocytes, microtubules predominantly reside in the cell body and main processes, whereas microfilaments are organized as an extensive network that extends from the cell body into peripheral branches and thin villi (Song et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Localization studies have demonstrated that actin and ERM (ezrin, radixin, and moesin) proteins, which are initially diffusely distributed, concentrate at either end of the Schwann cell just before myelination (Melendez-Vasquez et al, 2001;Pedraza et al, 2001) at tips of the cell that are dynamically active (Gatto et al, 2003). Actin microfilaments are also enriched in the processes of immature oligodendrocytes and, together with myosin IIB, are concentrated at the leading edges (Kachar et al, 1986;Wilson and Brophy, 1989;Song et al, 2001).…”
Section: Introductionmentioning
confidence: 99%